LOS FUNDAMENTOS DEL ÉXITO DE LAS EMPRESAS FAMILIARES EN EL PERÚ - Hinostroza Garamendi, Luis Rubén (2011)
This research has as an objective of testing and analyzing the concepts of the Family-Enterprise and the principles of success of Peruvian family-enterprises, which have been chosen as most successful companies as models to follow, putting to disposal of new enterpreunors whose dream is to constitute or start a company or for company owners who want to improve their businesses, applying the foundations that were used by successful Peruvian family-enterprises, like Romero Group, Brescia Group, Buenaventura Group, Gloria Group, Bembos, Topy Top, Lindley Corporation, Graña y Montero Group, Cerámicos Peruanos S. A. – Ladrillos Pirámide and Famall Group SAC. The decisive factors for their expansion, consolidation and growth, is based in identification of their foundation of family-enterprise success that have let them to be more competitive and to lead in the different segments of the market, generating more opportunities of job in our country. In this study, a survey to executives of ten family-enterprises was carried out in order to know the foundations of the success of these companies. Such survey was divided in two sections. The first one is related to the demographic data, and the second, to the foundations of the success of the familyenterprises. In that way, interviews and witnesses applied to family-enterprises. From the groups mentioned above, the results of this research found that the success was based in the innovation of new products and services, passion for excellence, the orientation to the results, values, loyalty, team work, commitment degree, technology of information and communications, the importance of human resources, professionalization, skills, creativity, identification, and management capacity as the key of success of the Peruvian family – enterprises.